2008
DOI: 10.1007/s10329-008-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Gibbons under seasonal stress: the diet of the black crested gibbon (Nomascus concolor) on Mt. Wuliang, Central Yunnan, China

Abstract: The diet of a habituated group of black crested gibbon (Nomascus concolor jingdongensis) was studied from March 2005 to April 2006 in the Wuliang Mountains, central Yunnan, China. Gibbons consumed 77 different plant species, one mammal-, two bird-, one lizard-, and two insect-species. Buds and leaves constituted 46.5% of the diet (21.0% vine leaves and buds, 19.2% tree leaves and buds, and 6.3% epiphyte leaves). Fruits, figs and flowers accounted for 25.5, 18.6 and 9.1% of the diet, respectively. There was mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 12 publications
3
59
1
Order By: Relevance
“…Gibbons spent approximately equal mean percentages of time eating fruit (44.1%) and leaves (46.5%, Fan et al 2008). Their diets varied significantly across months (Kruskal-Wallis test: χ 2 =18.067, p=0.000; Table 1).…”
Section: Diet and Activity Budgetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gibbons spent approximately equal mean percentages of time eating fruit (44.1%) and leaves (46.5%, Fan et al 2008). Their diets varied significantly across months (Kruskal-Wallis test: χ 2 =18.067, p=0.000; Table 1).…”
Section: Diet and Activity Budgetsmentioning
confidence: 99%
“…High rates of rest among crested gibbons may be due to differences in diet. Compared with the diet of other gibbons (Bartlett 2007), black-crested gibbons ate less fruit and more leaves (Fan et al 2008). As a food class, leaves contain less available calories and more indigestible fiber than those of fruits (Raemaekers 1978).…”
Section: Activity Patternmentioning
confidence: 99%
“…Members preferred fruit when it was available, although they spent nearly equal time feeding on fruit (figs) and on buds and leaves [Fan et al, 2009b]. Two fruit species that were seasonally important (defined as the minimum number of foods comprising 75% of the diet for each month [Fan et al, 2009b]), Choerospondias axillaria and Actinidia callosa , were mostly distributed below 2,100 m, and gibbons would visit them while they were fruiting. The gibbons rarely ranged below 2,100 m when these species were not fruiting.…”
Section: Effect Of Human Disturbance On the Ranging Patternmentioning
confidence: 99%
“…orangutans: Knott & Kahlenberg, 2007;gibbons: Bartlett, 2007], mangrove forest [proboscis monkeys : Bismark, 2010], to temperate forests [Yunnan snub-nosed monkeys: Xiao et al, 2003; Japanese macaques: Hanya, 2004] and grassland [geladas: Iwamoto & Dunbar, 1983]. Foraging animals therefore are required to make decisions regarding which resources to exploit, in order to ensure that they obtain sufficient nutrition and maintain good health [Bartlett, 2009;Fan et al, 2009;McConkey et al, 2003;Pavelka & Knopff, 2004;Stone, 2007]. Even in tropical regions close to the equator, seasonal differences in mean temperature are small but fluctuation in rainfall may be marked, which produces seasonal availability of food resources [Matsuda et al, 2009;McConkey et al, 2003;Pavelka & Knopff, 2004;Stone, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, temperate primates may switch to poorer quality food sources in the lean season [Fan et al, 2009;Poulsen et al, 2001;Xiang et al, 2007], resulting in more time spent feeding in order to compensate for reduced nutritional value [Bartlett, 2009;Nakagawa, 1989]. Moreover, animals living at higher latitudes experience seasonal changes not only in food availability but also ambient temperature [Bartlett, 2009;Fan et al, 2009;Hill, 1997], resulting in energetic challenges associated with thermoregulatory costs [Hanya, 2004]. Nakayama et al [1971] reported that the energy expenditure of outdoor-living captive Japanese macaque (Macaca fuscata) at 5.2 • C is 2.5 times greater than that at 29.5 • C. To save energy, Japanese macaques decrease traveling and feeding when the temperature is low and the thermoregulatory costs are severe [Hanya, 2004].…”
Section: Introductionmentioning
confidence: 99%